Ghost horses : a mystery in Zion National Park - Skurzynski, Gloria; Ferguson, Alane (Washington, D.C. : National Geographic, 2007)
Visiting Zion National Park with his family, twelve-year- old Jack encounters two mysteries, the strange behavior of a band of wild mustangs and the possibly sinister actions of his new foster brother, a Shoshone boy.
Accelerated Reader AR
Keywords: Wild horses -- Juvenile fiction; Horses -- Juvenile fiction; Shoshoni Indians -- Juvenile fiction; Indians of North America -- Juvenile fiction; Foster home care -- Juvenile fiction; National parks and reserves -- Juvenile fiction; Mystery and detective stories; Zion National Park (Utah) -- Juvenile fiction; Utah -- Juvenile fiction